Fire structures in the Buenos Aires coastline (Bahía San Blas, provincia de Buenos Aires, Argentina): A physical-chemical analysis interpretation - Aldazabal, Veronica Beatriz (2015)
Archaeological investigations carried out in the area of San Blas Bay revealed a great number of surface concentrations of shells, lithic artifacts and in lesser amount, ceramic remains. These places have been occupied by hunter-gatherers from the middle Holocene to recent times. In some cases, cultural materials and combustion structures have been reported in stratigraphic position. In this paper, we present the analysis of a hearth in a cup shape structure located in a sand aeolian deposit, in the La Serranita archaeological site, dated from 5300. BP, compared with another hearth from Las Olas 5 site, dated from 500. BP. The aim is to infer the activities that could be carried out in relation to the combustion structures, by physical-chemical analysis of sediments, and by identifying and quantifying the microremains. An attempt is made to determine the intensity of use of the fire structures.